An Aumann-Shapley approach to bilateral transmission loss pricing in a gross-pool energy market using independent marginal losses and transaction loss factors - Zaño, Rienzi Ofreneo (2010)
Transmission loss is an intrinsic characteristic of a power system. It accounts to approximately 2-6% of total electrical energy produced for a large power system. In a mixed pool/bilateral, LMP (Locational Marginal Price) based energy market, each participant, i.e., either the Generating Company (GenCos) or the Distribution Utilities (DU) must pay its share in the losses of the transmission network. For multiple Generator-Load pair bounded by a physical bilateral contract, these losses must be accounted for accordingly. A transaction-based loss allocation technique which uses a Transaction Loss Factor (TLF) coupled with the newly developed Independent Marginal Loss (IML) formulation and Aumann-Shapley methodology was used in this study to determine the bilateral loss cost allocation. The TLF accurately and fairly allocates loss for each bilateral transaction, the IML solves the reference bus dependency of the marginal loss sensitivity while the Aumann-Shapley from game theory tackles the multiple ?entrant, joint cost allocation problem.